Modification of interface anisotropy and its effect on microstructural evolution during ostwald ripening. Issue 11 (13th September 2013) - Singh, N. B.; Berghmans, A.; King, M.; Knuteson, D.; Talvacchio, J.; Kahler, D.; House, M.; Schreib, B.; Wagner, B.; McLaughlin, S.
<x xml:space="preserve">Abstract</x> Large screw dislocation steps on the surface of the faceted grain. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>